ANHA DOTHRAK CHEK ASSHEKH: THE RENDERING OPERATION OF THE INVENTED LANGUAGE DOTHRAKI INTO BAHASA INDONESIA IN GAME OF THRONES SEASON 6 - Isnaini, Anisa Wahyu (CrossOver, 2024)
This research is conducted to observe the rendering operation of L3 translation applied of Game of Thrones series Season 6, specifically focusing on two objectives: identifying the types of rendering operations used and explaining why these operations are chosen. The research adopts a descriptive qualitative approach. Corrius and Zabalbeascoa's theory on L3 translation rendering operations serves as the framework for addressing the research questions. Data analysis employs Spradley’s componential analysis method, and the researcher verified the findings with an expert. The study identified 175 instances of Dothraki language in Game of Thrones Season 6, leading to the discovery of three distinct types of L3 translation rendering operations. There are 6 Delete L3ST (3,5%) in which the L3 in ST is omitted in TT, 16 Substitute L3ST → L2 (9,1%), which is divided into 2 conditions. There are condensation and inappropriate translation. The last is 153 Substitute L3ST (87,4%) which is divided into two conditions, defining the plot and emphasizing the characters, identity and story. The data shows that the most dominant rendering operation of L3 translation applied by the subtitler is Substitute L3ST because it is considered to be the most suitable operation that can be used as a solution in translating invented language. It is also because the subtitler accurately translated the third language into the target language, as evidenced by the consistency with the dictionary, dialogues, and scene narratives. The second finding of this research shows that there are 2 kinds of nature and degree of L3 presence. In this research, the researcher found 22 data (12,6%) of Lost which is divided into 6 causes, i.e: lack of duration, no full translation, accidental error, incorrect translation, unnecessary scene and unclear words. Also 153 data (87,4%) of Kept which is divided into 4 conditions; to define Khaleesi, define Dothraki, define Game of Thrones and define the context of the story. This means that the subtitler still wants to retain the meaning and the style of the third language.